Topical delivery of extracted curcumin as curcumin loaded spanlastics anti-aging gel: Optimization using experimental design and ex-vivo evaluation - Rania El Hosary; Mahmoud H. Teaima; Mohamed El-Nabarawi; Yousra Yousry; Mahmoud Eltahan; Ahmed Bakr; Hussein Aboelela; Rehab Abdelmonem; Rafik M. Nassif (Elsevier, 2024)
Objective: This study aimed to extract and separate the organic coloring agent known as Curcumin from the rhizomes of Curcuma longa, and then to create Spanlastics that were loaded with curcumin using the ethanol injection technique. The optimized Spanlastic dispersions were then incorporated into a gel preparation for topical anti-aging use. The Spanlastic dispersions were analyzed for particle size, zeta potential, drug loading efficiency, and in vitro release profile. Furthermore, the rheological properties of the gel preparation were assessed, and a skin penetration study was conducted using confocal microscopy. Methods: Twelve different Curcumin-loaded Spanlastic dispersions using the ethanol injection method with Span® 60 as a surfactant and Tween® 80 as an edge activator in varying ratios. The dispersions were then subjected to various tests, such as particle size analysis, zeta potential measurement, drug entrapment efficiency assessment, and in vitro release profiling. The optimized formula was selected using Design-Expert® software version 13, then used to create a gel preparation, which utilized 2% HPMC E50 as a gelling polymer. The gel was evaluated for its rheological properties and analyzed using confocal microscopy. Additionally, Raman analysis was performed to ensure that the polymers used in the gel were compatible with the drug substance. Results: F5 formula, (that contains 10 mg Curcumin, and mixture 5 of span-tween mixtures that consist of 120 mg Span® 60 with 80 mg Tween® 80) was selected as the optimized formula with a desirability produced by Design Expert® software equal to 0.761, based on its particle size (212.8 ± 4.76), zeta potential (−29.4 ± 2.11), drug loading efficiency (99.788 ± 1.34), and in vitro release profile evaluations at Q 6hr equal to almost 100 %. Statistical significance (P < 0.05) was obtained using one-way ANOVA. Then F5 was used to formulate HPMC E50 gel-based preparations. The gel formula that was created and analyzed using Raman spectroscopy demonstrated no signs of incompatibility between the Curcumin and the polymers that were utilized.The confocal spectroscopy found that the anti-aging gel preparation showed promising results in terms of skin penetration. Also, images revealed that the gel could penetrate the layers of the skin (reached a depth of about 112.5 μm), where it could potentially target and reduce the appearance of fine lines and wrinkles. The gel also appeared to be well-tolerated by the skin, with no signs of irritation or inflammation observed in the images. Conclusion: The obtained results successfully confirmed the potential of the promising (F5) formula to produce sustained release action and its ability to be incorporated into 2% HPMC E50 anti-aging gel. The confocal microscopy study suggested that the anti-aging gel had the potential to be an effective and safe topical treatment for aging skin.